Problemas familiares y su relación con el desarrollo emocional en los estudiantes del primer año de secundaria de la I.E Nª 20335 “nuestra señora del Carmen”- Huaura - León Requena, Yeremi Yanina (2021)
The research on FAMILY PROBLEMS AND ITS CORRESPONDENCE WITH EMOTIONAL DEVELOPMENT IN THE SCHOOLS OF THE FIRST YEAR OF SECONDARY YEAR N º 20335 “NUESTRA SEÑORA DEL CARMEN” - HUAURA, the methodology of basic, expressive, correlational, non-experimental research was used and the Assumption was family difficulties are significantly concerned with emotional development in schoolchildren of the first year of high school at EI No. 20335 Our Lady of Carmen-Huaura. The population was 545 high school students, for which, the sample was determined by coexistence of 129 students of the first year. The expertise was the inquiry and the tool the interrogation, applied to the first and second variables. The results show the correspondence of family difficulties and emotional development in schoolchildren of the first year of secondary school at I.E No. 20335 Our Lady of Carmen-Huaura, of moderate magnitude